1988
DOI: 10.1111/j.1944-9720.1988.tb03119.x
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Reading Strategies: How Methodology Affects Language Course Articulation

Abstract: This study examines whether university‐level French students trained during the second semester to use effective reading strategies and skills demonstrate better reading comprehension and, hence, perform better in the third semester than their untrained peers. The experimental reading activities were derived from recent L1 and L2 reading process theory and research; a sample text, exercises, and lesson plan appear together with teacher and student reactions to the experimental reading practice. These self‐repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…The students who participated in the study showed the motivation and attraction during the training sessions based on speed reading strategies which agreed with the theoretical background of the same studies like Broughton et al (1980), Bever and Bover (1970) and Waldman (1972) about the importance of using speed reading strategies to improve the students' comprehension The results of the study agreed with Baunann's (1984), Barnett's (1988) and Rababa'h's (1991) results in their studies of training students on comprehension skill to get the main idea. The result approved what Mackenzie (2011) clarified about the thinking through reading comprehension strategies that should follow the following steps : Making Connections, Retelling, Visualizing, Asking Questions, Making Predictions, Making Inferences, Understanding Text Structure, Determining Importance, Identifying the Author's Message, and Synthesizing.…”
Section: Discussion Of the Resultssupporting
confidence: 81%
“…The students who participated in the study showed the motivation and attraction during the training sessions based on speed reading strategies which agreed with the theoretical background of the same studies like Broughton et al (1980), Bever and Bover (1970) and Waldman (1972) about the importance of using speed reading strategies to improve the students' comprehension The results of the study agreed with Baunann's (1984), Barnett's (1988) and Rababa'h's (1991) results in their studies of training students on comprehension skill to get the main idea. The result approved what Mackenzie (2011) clarified about the thinking through reading comprehension strategies that should follow the following steps : Making Connections, Retelling, Visualizing, Asking Questions, Making Predictions, Making Inferences, Understanding Text Structure, Determining Importance, Identifying the Author's Message, and Synthesizing.…”
Section: Discussion Of the Resultssupporting
confidence: 81%
“…Closely related to understanding the nature of reading is recognizing the influence of metacognitive awareness and strategy training. Research (Barnett, 1988a(Barnett, , 1988bCarrell, 1989;Swaffar, Arens, & Byrnes, 1991) suggests that understanding the process and then working to modify one's behavior improves L2 r e a d i n g comprehension. I n this way, students can better learn to transfer their L1 reading ability and to draw on compensatory factors such as contextual a n d formal schemata t o overcome the barr i e r of l i m i t e d l a n g u a g e c o m p e t e n c y a n d , thereby, to short circuit the short-circuit effect of the language threshold.…”
Section: Discussionmentioning
confidence: 99%
“…In a later study, Carrell, Pharis, & Liberto (1989) showed that strategy training with semantic mapping and with the ETR (experience, text, relationship) method both improved reading comprehension scores. Barnett (1988a) reported improvement in reading comprehension from a year-long strategy training experiment in reading. In a related experiment over one semester (Barnett, 1988b), however, she did not see significant improvement in the training group.…”
Section: Comprehension Strategy Instructionmentioning
confidence: 99%